A Research on Awareness Level of Ahmet Piriştina İzmir City Archive and the Museum (APİKAM) in the Town, as the Earliest Form of Turkey - Mehmet Ali Akkaya (Türk Kütüphaneciliği)
City archives and city museums are one of the most important institutions that take an active role in creating city and urbanism awareness and protecting the cultural heritage and transmitting it to the posterity. Ahmet Piriştina İzmir City Archive and the Museum (APİKAM) that put into service in 2004 is the first sample in this area of Turkey. In this study; it has been aimed to reveal the awareness level of APİKAM and contribute to answer the questions related to how service quality increases. 7-item survey created in this context has been answered by 568 city-dwellers with face to face meeting. Feedbacks show that though there is a high level of visitor satisfaction, APİKAM doesn’t come to be known enough by the city-dwellers, as for those who are aware of the institution are not eager to visit it. When taking into consideration the habitants’ general approaches with regard to city archive and museum or their lack of need of visiting the museum, it is clear that there is a long way to come in order to increase the awareness level of APİKAM.